Question

# Write the product in standard form. (𝑥 − 4)(𝑥 + 4)

## The correct answer is: 16

### (𝑥 − 4)(𝑥 + 4) = 𝑥(𝑥 + 4) − 4(𝑥 + 4)

= 𝑥(𝑥) + 𝑥(4) - 4(𝑥) - 4(4)

= 𝑥^{2} + 4𝑥 - 4𝑥 - 16

= 𝑥^{2} - 16

Final Answer:

Hence, the simplified form of (𝑥 − 4)(𝑥 + 4) is 𝑥^{2} - 16

This question can be easily solved by using the formula

(a + b)(a - b) = a2 - b2

### Related Questions to study

### The area of the rectangle is 𝑥^{2} + 11𝑥 + 28. Its length is x + __ and its width is __+ 4. Find the missing terms in the length and the width.

### The area of the rectangle is 𝑥^{2} + 11𝑥 + 28. Its length is x + __ and its width is __+ 4. Find the missing terms in the length and the width.

### Simplify: 12 - [13a - 4(5a -7) - 8 {2a -(20a - 3a)}]

### Simplify: 12 - [13a - 4(5a -7) - 8 {2a -(20a - 3a)}]

### Write the product in standard form. (2𝑥 + 5)^{2}

This question can be easily solved by using the formula

(a + b)2 = a2 + 2ab + b2

### Write the product in standard form. (2𝑥 + 5)^{2}

This question can be easily solved by using the formula

(a + b)2 = a2 + 2ab + b2

### Write the product in standard form. (𝑥 − 7)^{2}

This question can be easily solved by using the formula

(a - b)2 = a2 - 2ab + b2

### Write the product in standard form. (𝑥 − 7)^{2}

This question can be easily solved by using the formula

(a - b)2 = a2 - 2ab + b2

### (𝑥 + 9)(𝑥 + 9) =

This question can be easily solved by using the formula

(a + b)2 = a2 + 2ab + b2

### (𝑥 + 9)(𝑥 + 9) =

This question can be easily solved by using the formula

(a + b)2 = a2 + 2ab + b2

### Find the area of the rectangle.

### Find the area of the rectangle.

### The table below shows the distance a train traveled over time. How can you determine the equation that represents this relationships.

### The table below shows the distance a train traveled over time. How can you determine the equation that represents this relationships.

### Simplify: 4x^{2}(7x -5) -6x^{2}(2 -4x)+ 18x^{3}

### Simplify: 4x^{2}(7x -5) -6x^{2}(2 -4x)+ 18x^{3}

### (𝑎 + (−3))^{2} =

This question can be easily solved by using the formula

(a - b)2 = a2 - 2ab + b2

### (𝑎 + (−3))^{2} =

This question can be easily solved by using the formula

(a - b)2 = a2 - 2ab + b2

### Use the table method to multiply a binomial with a trinomial.

(−3𝑥^{2} + 1) (2𝑥^{2} + 3𝑥 − 4)

### Use the table method to multiply a binomial with a trinomial.

(−3𝑥^{2} + 1) (2𝑥^{2} + 3𝑥 − 4)

### (𝑥 − 2)^{2} =

This question can be easily solved by using the formula

(a - b)2 = a2 - 2ab + b2

### (𝑥 − 2)^{2} =

This question can be easily solved by using the formula

(a - b)2 = a2 - 2ab + b2